Internalization of Religious Moderation Values in Learning Strategies Within Pasraman Non-Formal Education in Mataram - Wiguna, Ida Bagus Alit Arta; Andari, Ida Ayu Made Yuni (Jayapangus Press, 2025)
Indonesia, with its religious, ethnic, and cultural diversity, faces great challenges in maintaining harmony between religious communities. Pasraman, as a non-formal educational institution that teaches Hinduism, has an important role in instilling the values of religious moderation in the younger generation. This study aims to analyse the learning strategy of religious moderation in pasraman, Mataram City, and the impact of internalising these values on sisyas. The method used is qualitative descriptive with a case study approach. Data was collected through in-depth interviews, direct observations, and documentation studies in several active pasramans in Mataram. The study results show that pasraman implements five main learning strategies system-oriented, expositive, cooperative, contextual, and affective. This strategy focuses on teaching the values of tolerance, respect for differences, and social harmony. Despite challenges such as a limited understanding of Acarya and limited facilities, the study's results revealed that the value of religious moderation has succeeded in shaping the character of sisya, who are more open, tolerant, and ready to contribute to a multicultural society. This research contributes to developing Hindu religious education based on religious moderation in Indonesia, especially in increasing tolerance and harmony in a plural society.